Souperchicken - Auch, Mary Jane.; Auch, Herm (New York : Holiday House, 2003)
When Henrietta becomes the first chicken in her coop to learn how to read, she uses her skills to save her aunties from becoming chicken soup.
G2
Keywords: Chickens -- Fiction; Domestic animals -- Fiction; Reading -- Fiction